6
$\begingroup$

This is from the book Fundamentals of Probability with Stochastic Processes by Saeed Ghahramani, pages 249-250 which asserts, for any random variable $X$ that is non-negative, expectation of $X$ is

$$ E(X)= \int_{0}^{\infty} [1-F(t)]dt= \int_{0}^{\infty} P(X>t) dt $$

Where $F(t)$ is a cumulative distribution function. Somehow this is equal to $\int_{0}^{\infty}x. P(X=x)dx$ and I don't see it.Though the proof is provided in the book, I find it lacking and wasn't completely satisfied with it.

I would like to see a proof of the discrete analog of the above expression

$$ E(X) = \sum_{x=0}^{\infty}x. P(X=x)= \sum_{x=0}^{\infty} [1- F(x)] = \sum_{x=0}^{\infty} \sum_{y=0}^{x} P(Y=y) $$

This is a very basic probability question.

$\endgroup$
8
$\begingroup$

The discrete case, assume that $X \ge 0$ takes non-negative integer values. Then we can write the expectation as $$ \DeclareMathOperator{\E}{\mathbb{E}} \DeclareMathOperator{\P}{\mathbb{P}} \E X = \sum_{k=0}^\infty k \P(X=k) $$ Now, we will first write this as a double sum, and then change the order of summation. Observe that $k = \sum_{j=0}^{k-1} 1$ (the case $k=0$ gives a lower upper than lower limit, we take that as the empty sum, which is zero). This gives $$ \E X = \sum_{k=0}^\infty \sum_{j=0}^{k-1} 1 \cdot \P(X=k) $$ Now, in this double sum we sum first on $j$, which clearly goes to $\infty$. Observe that in the inner summation the indices satisfy the inequality $$ 0 \le j \le k-1 $$ Solving that for $k$ gives $ k \ge j+1$, which then gives the limits of summation in the new inner sum: $$ \E X = \sum_{j=0}^\infty \sum_{k=j+1}^\infty \P(X=k) = \sum_{j=0}^\infty \P(X > j) $$ which is the result. The continuous case is similar.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.